Effectiveness of Lumbosacral Orthosis After Discectomy for Lumbar Disk Herniation: A Prospective Comparative Study. Issue 1 (1st January 2023) - Sakaki, Kyohei; Yoshii, Toshitaka; Arai, Yoshiyasu; Torigoe, Ichiro; Tomori, Masaki; Onuma, Hiroaki; Ogawa, Takahisa; Hirakawa, Akihiro; Sakai, Kenichiro; Okawa, Atsushi
Abstract : Study Design: A prospective comparative study. Objective: To investigate the benefits of postoperative application of lumbosacral orthosis after single-level discectomy for lumbar disk herniation (LDH). Summary of Background Data: Although many surgeons use postoperative lumbosacral orthosis for patients with LDH, there is no clear evidence to support or deny its effectiveness. Materials and Methods: Ninety-nine consecutive patients who underwent the microscopic discectomy were included. They were divided into two groups: orthosis group and nonorthosis group, before surgery. The recurrence rate and reoperation rate were compared between the two groups at four-week, six-month, and one-year follow-up. Japanese Orthopaedic Association Score for lumbar spine (L-JOA score) at two-week and one-year follow-up, lower extremities and low back pain's visual analog scale (VAS) and Oswestry Disability Index (ODI) at six-month and one-year follow-up were compared. Results: Forty-two patients in the orthosis group and 39 patients in the nonorthosis group were followed up for at least one-year after surgery. Recurrence occurred in three patients (7.1%) in the orthosis group and six (15.4%) in the nonorthosis group within one-year. Two patients (4.8%) in the orthosis group and two patients (5.1%) in the nonorthosis group underwent reoperation. There were no significant intergroup differences in the recurrence rate and in the reoperation rate. No significant difference was also observed between the two groups in L-JOA score, ODI, VAS of low back pain, and leg pain at one-year after surgery. Furthermore, at any other follow-up period, no significant differences were observed between the two groups in recurrence rate, reoperation rate, L-JOA score, VAS of low back/leg pain, or ODI. Conclusions: The use of a postoperative orthosis did not reduce recurrence or reoperation rates, nor did it improve postoperative clinical symptoms. The routine use of an orthosis may not be necessary after single-level lumbar discectomy.